An Investigation of Students Phonological Awareness in Speaking - Ika Sastrawati; Haslinda Haslinda; Salma Salma; Fadillah N; Ibrahim R (BATARA DIDI : English Language Journal, 2023)
The study is designed to address the fundamental question of how students understand phonological awareness. Learning to read is based on phonological awareness, the purpose for the student to be able to recognize the sounds of the spoken language, which of course enables the recognition of the spoken voice. In this case, speaking, which is one of the most important English language skills, also plays an important role, and the thought processes of languages are interconnected. The research used in this context was a quantitative method. Third-semester students of Universitas Muhammadiyah Makasssar were used as subjects, but only five students became research subjects to understand phonological awareness. The medium used in this study was a text medium. All correspondents used English. Based on the results of the study, it was revealed that three out of five subjects understood the four indicators of phonological awareness and two of them understood very little or did not understand the four indicators of phonological awareness. This shows that understanding students who were the subject of the third semester of the English Language Education study program already good and the total number of research results is 77.5 or in terms of quality was good.